Geomorphological analysis using small unmanned aerial vehicles and submeter GNSS (Gara Soultana butte, High Plateaus Basin, Eastern Morocco). Issue 2 (9th December 2020) - Benito-Calvo, A.; Haddoumi, H.; Aouraghe, H.; Oujaa, A.; Chacón, M.G.; Sala-Ramos, R.
ABSTRACT: The High Plateaus Basin is an important region to understand landscape evolution and human occupation in North Africa during the Quaternary. We focused on the Gara Soultana area, applying Unmanned Aerial Vehicles, photogrammetry and a submeter Global Navigation Satellite System, for large scale geomorphological mapping. This work in the upper Moulouya catchment has allowed us to define the landform sequence. Conglomerate platforms previously considered to be fluvial terraces, are interpreted here as exhumed bedrock layers of the Plio-Pleistocene stacked series. The El Haï river incision consists of a first phase, represented only by the exhumation of Gara Soultana butte, and a second phase when five strath terraces developed from +20-22 m to the thalweg, formed since the Middle Pleistocene. Holocene terraces could be associated with brief aggradation phases in the lower Moulouya catchment due to rapid climate changes. Fluvial incision led to the formation of mantled pediments and talus flatirons.